Open.Ed – OER and Open Knowledge at the University of Edinburgh - Campbell, Lorna; Farley, Charlie (My University, 2018)
Open.Ed (http://open.ed.ac.uk/) is the University of Edinburgh’s Open Educational Resources (OER) Service which supports staff and students to engage with the use and creation of OER and open knowledge to enhance the quality of the student experience and make a significant contribution to the digital and cultural commons. At the University of Edinburgh, we believe that OER and open knowledge are strongly in line with our institutional mission to provide the highest quality learning and teaching environment for the greater wellbeing of our students, and to make a significant, sustainable and socially responsible contribution to Scotland, the UK and the world, promoting health and economic and cultural wellbeing. Supported by an institutional OER Policy, the University’s vision for OER builds on our excellent education and research collections, traditions of the Scottish Enlightenment and the university’s civic mission. Open.Ed also provides digital skills training and an open showcase for a diverse range of open educational resources created by staff and students around the University. This 10x10 presentation will introduce the University of Edinburgh’s OER policy, vision and service and highlight a range of resources, activities and initiatives it supports including the award winning 23 Things for Digital Knowledge open course, the work of our Open Content Curation interns, Geosicences outreach and engagement resources, OER for equality and diversity, playful approaches to supporting open education including Board Game Jam and Gif It Up, creative use of open film snippets, and innovating with open knowledge.
Keywords: Open Educational Resources